Comparative analysis of mitochondrial genomes among the family Peltoperlidae (Plecoptera: Systellognatha) and phylogenetic implications - Wang, Ying; Cao, Jinjun; Guo, Xuan; Guo, Caiyue; Li, Weihai; Murányi, Dávid (Frontiers in Ecology and Evolution, 2022)
Nowadays, the position of Peltoperlidae in Systellognatha has been resolved based on morphological analyses. However, there are different opinions based on molecular data. To date, only three peltoperlid mitogenomes are available, and more sampling is needed to obtain precise phylogenetic relationships. In this study, we obtained the complete mitogenomes of Cryptoperla kawasawai (15,832 bp) and Peltoperlopsis sagittata (15,756 bp). Our results show that gene content, gene order, DmTTF binding site, nucleotide composition, codon usage, RNA structure, and structural elements in the control region are highly conserved in peltoperlids. Heatmap analysis of codon usage shows that the AT-rich codons UUA, AUU, UUU, and AUA were commonly used codons in the Peltoperlidae. Evolutionary rate analyses of protein-coding genes reveal that different genes have been subject to different rates of molecular evolution correlated with the GC content. All tRNA genes in peltoperlid mitogenomes have a canonical cloverleaf secondary structure except for trnS1, whose dihydrouridine arm simply forms a loop. The control region of the family has several distinct structural characteristics and has the potential to serve as effective phylogenetic markers. Phylogenetic analyses support the monophyly of Perloidea, but the monophyly of Pteronarcyoidea is still not supported. The Peltoperlidae is placed as the earliest branch within the Systellognatha, and the estimated phylogenetic relationship is: Peltoperlidae + ((Styloperlidae + Pteronarcyidae) + (Perlidae + (Chloroperlidae + Perlodidae))). Our results provide new insight into the phylogeny of this group.